A rapid fluorescent indicator displacement assay and principal component/cluster data analysis for determination of ligand–nucleic acid structural selectivity - del Villar-Guerra, Rafael (Nucleic Acids Res, 2018)
We describe a rapid fluorescence indicator displacement assay (R-FID) to evaluate the affinity and the selectivity of compounds binding to different DNA structures. We validated the assay using a library of 30 well-known nucleic acid binders containing a variety chemical scaffolds. We used a combination of principal component analysis and hierarchical clustering analysis to interpret the results obtained. This analysis classified compounds based on selectivity for AT-rich, GC-rich and G4 structures. We used the FID assay as a secondary screen to test the binding selectivity of an additional 20 compounds selected from the NCI Diversity Set III library that were identified as G4 binders using a thermal shift assay. The results showed G4 binding selectivity for only a few of the 20 compounds. Overall, we show that this R-FID assay, coupled with PCA and HCA, provides a useful tool for the discovery of ligands selective for particular nucleic acid structures.